THE INTERACTION BETWEEN READING COMPETENCY AND PROBLEM-SOLVING SKILLS IN SECONDARY EDUCATION STUDENTS - Antonio María Rodríguez Abello; Diego Arley Marulanda Patiño (LÍNEA IMAGINARIA, 2026)
This essay-style article analyzes the intimate connection between the ability to read with understanding and problem-solving skills, two essential competencies for the academic and personal success of secondary school students. Through a theoretical examination and a review of recent research, it investigates how text comprehension affects the development of critical thinking and problem-solving skills at this educational level. The results suggest that strong reading skills provide cognitive tools, such as extensive vocabulary, the ability to make inferences, and self-regulation, which are essential for understanding and managing complex situations, while the practice of problem-solving strengthens critical reading. It also highlights that contextual factor, such as educational quality, inclusive strategies such as translanguaging in bilingual classrooms, and the availability of technological and bibliographic resources, are crucial for enhancing both skills and reducing socioeconomic disparities. Based on these results, integrated educational strategies are suggested, such as including reading comprehension in all subjects, training teachers in approaches that combine reading and critical thinking, ensuring equitable access to resources, and using active methodologies such as project-based learning (PBL). Therefore, research shows a synergistic relationship between reading comprehension and problem-solving and promotes a comprehensive pedagogical approach that simultaneously strengthens these fundamental skills in young people.